A lurking ambivalence: The discourse on female taiyupian stars' experiences in Hong Kong. Issue 2 (31st July 2020) - Wang, Chun-Chi
Abstract: This paper analyses the transnational careers of taiyupian female stars, who, during the first downturn in taiyupian production during the late 1950s and early 1960s, travelled to Hong Kong to make Amoy-dialect films. This collaboration contributed to a transnational Hokkien ethnic film culture and has been claimed for the formation of a Hokkien-identified cultural sphere. However, a closer examination of star discourses surrounding their experiences of working and living in Hong Kong reveals ambivalence that complicates this proposition. This paper argues that the shared ethnic Hokkien heritage that enabled co-productions is complicated by an implicit unease toward modernity as well as market competition between the film industries in Taiwan and Hong Kong.